Про еквiвалентнiсть збурень оператора диференцiювання функцiями вiд оператора Помм’є - Linchuk, Yu. S. (Reports of the National Academy of Sciences of Ukraine, 2016)
We establish the conditions of equivalence of two operators that are perturbations of the differential operator by functions of the Pommiez operator in the spaces of functions analytic in arbitrary starlike domains of the complex plane with respect to the origin. We describe the commutants of the operators and establish their hypercyclicity and chaoticity.